Pretreatment of hepatetctomized rats with Coleus forskohlii did not interfere with the course of hepatic hyperplasia - Barros,Pedro Paulo (2019)
Abstract Purpose Coleus forskohlii Briq., a medicinal plant originally from India, has been indicated against heart disease, expiratory disorders, convulsions, and hepatic changes, among others. In view of the broad pharmacological potential of the plant and the scarce information about its effects, the objective of the present study was to investigate the effect of its use for pretreatment of partially hepatectomized rats. Methods The animals were divided into two experimental groups: Control (CG) receiving physiological saline for 10 days before partial hepatetctomy, and Treated (TG) receiving 40 mg Coleus forskohlii/kg/day for 10 days before partial hepatectomy. The treatments were performed by gastric gavage. After the surgical procedure, treatment was continued according to the following groups: CG 24 h, CG 48 h, TG 24 h, and TG 48 hs, and liver tissue and intracardiac blood samples were obtained for histological and biochemical analysis, respectively. Results No significant differences were observed in mitotic or apoptotic index or in the concentrations of the enzymes AST, ALT and alkaline phosphatase, and no areas of fibrosis were detected. Conclusion Treatment with Coleus forskohlii did not interfere with the course of hepatic hyperplasia.